Humans can separately perceive distance, velocity, and acceleration from vestibular stimulation - Heyde, M. von der; Riecke, B. E.; Cunningham, D. W.; Bülthoff, H. H. (3. Tübinger Wahrnehmungskonferenz (TWK), 2000)
Purpose: The vestibular system is known to measure changes in linear and angular position changes in terms of acceleration. Can humans judge these vestibular signals as acceleration and integrate them to reliably derive distance and velocity estimates? Methods: Twelve blindfolded naive volunteers participated in a psychophysical experiment using a Stewart-Platform motion simulator. The vestibular stimuli consisted of Gaussian-shaped translatory or rotatory velocity profiles with a duration of less than 4 seconds. The full two-factorial design covered 6 peak accelerations above threshold and 5 distances with 4 repetitions. In three separate blocks, the subjects were asked to verbally judge on a scale from 1 to 100 the distance traveled or the angle turned, maximum velocity and maximum acceleration. Results: Subjects judged the distance, velocity and acceleration quite consistently, but with systematic errors. The distance estimates showed a linear scaling towards the mean response and were independent of accelerations. The correlation of perceived and real velocity was linear and showed no systematic influence of distances or accelerations. High accelerations were drastically underestimated and accelerations close to threshold were overestimated, showing a logarithmic dependency. Therefore, the judged acceleration was close to the velocity judgment. There was no significant difference between translational and angular movements. Conclusions: Despite the fact that the vestibular system measures acceleration only, one can derive peak velocity and traveled distance from it. Interestingly, even though maximum acceleration was perceived non-linearly, velocity and distance judgments were linear.
Keywords: Riecke; Riecke_2000; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; talkWithoutPaper